Association of osteopontin gene with milk production traits in Gir native and HF crossbred cows - D F, SHINGNE; M P, SAWANE; M M, CHOPADE; S D, SORTE; V D, PAWAR (The Indian Journal of Animal Sciences, 2024)
In the present investigation, relationship between bovine osteopontin (OPN) gene variants and milk production traits of Gir native and Holstein Friesian (HF) crossbred cattle was studied. A total number of 30 each from Gir native and HF crossbred cows were genotyped by using PCR-RFLP method. The BsrI/ PCR-RFLP analysis of 290 bp OPN Intron 4 amplicons revealed two genotypes (TT and CT) in Gir native cow while, three genotypes (TT, CT and CC) in HF cows. The observed genotypic and allelic frequencies were TT (0.63), CT (0.37) and T (0.82), C (0.18) for Gir native cows while, TT (0.20); CT (0.57); CC (0.23) and T (0.48); C (0.52) for HF crossbred cows, respectively. There was no significant association between OPN genotypes with the lactation milk yield and fat per cent of the cows studied. Molecular screening of the larger Gir and HF crossbred population might be helpful in discovering the association between OPN variants and milk traits in studied breeds.